IDEOLOGY IN CHOOSING A CODE FOR CHILDREN IN BALONGMOJO VILLAGE - Wiwik Mardiana (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2016)
This study aims at investigating children’s language use, factor motivating choosing language for children, and parents’ ideology as an influential factors in choosing a code. This study was conducted in Balongmojo Village. The data were language used by the children and interview result from the parents. The data were taken from 10 children of 5 to 10 years of age. In collecting the data the researcher used observation and interview method. The result of this study showed that the children’s language use and the tendency language chosen in Balongmojo village happens because of some factors covering the parents‘ ideology due to social need and parents‘ low proficiency of using JL and social factors—participants and setting—and attitudes and values as the result of parents‘ ideology. This also means that the parents attempt to find identity in social life.